HUBUNGAN PELAYANAN DOKTER TERHADAP PERSEPSI MUTU PASIEN PESERTA BPJS DI INSTALASI RAWAT JALAN RSUD ARIFIN ACHMAD PEKANBARU TAHUN 2015 - Natassa, Jihan; Arviana, Desma (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
According to indonesian lawno.44 2009 article 2 about the hospital said that hospitals must remain capableimprove services of better quality to fulfilledhighest degree of health.While according to indonesianlaw no 24 states that in 2011 about BPJS,BPJS aimed to provide certainty for social protection and welfare of all the people .The purpose of this research is to know the relationship of doctor servicesagainst the perception of patient qualityparticipants of BPJS in outpatient installation ArifinAchmad Hospital Pekanbaru 2015. The kind of this research is analytic quantitative research, with a design cross sectional. Research carried out time for the month ofmay-june 2015. Total Sample are 196 peopleswhichisthe participants of BPJS who is visiting out patient installation in ArifinAchmad Hospital Pekanbaru. The sample collection technique is accidental of sampling Analysis that been used is bivariat and univariat. From the results of research shows that there is meaningful relationship between medical doctor skills with perception of patients p value = 0,005 (p<alpha 0,05), The attitude of the doctor with patientsperception p value = 0,000 (p<alpha 0,05), Information dissemination doctor with patientsperceptionp value = 0,004 (p<alpha 0,05),Punctuality of doctorservicesp value = 0,005 (p<alpha 0,05). Can be concluded that there is the relationship between doctor services against the perception of patient quality participants of BPJS in outpatient installation ArifinAchmad Hospital Pekanbaru. Hence it is expected to chairman of hospital management in order to repair and improve quality of service doctor.